Selection of Lactobacillus strains from native chicken feces for the fermentation of purple onion (Allium cepa L.) as an antibiotic alternative against Salmonella spp. in chickens - Phan Vu Hai; Hoang Thi Anh Phuong; Pham Hoang Son Hung; Tran Thi Na; Ngo Huu Lai; Nguyen Dinh Thuy Khuong; Tran Ngoc Liem; Nguyen Xuan Hoa (Open Veterinary Journal)
Background: The increasing prevalence of antibiotic resistance in poultry pathogens necessitates the development of sustainable alternatives to antibiotics. Probiotics, particularly Lactobacillus spp., have shown promise in combating bacterial infections in poultry. Purple onion extract (OE) possesses antibacterial properties and can potentially enhance the probiotic efficacy of Lactobacillus strains.